The area of freedom, security and justice in the european union - Zeynalov, Rüstem (My University, 2009)
Bu tez Amsterdam antlaşması ile ortaya sunulan Avrupa özgürlük, güvenlik ve adalet bölgesi(AÖGAB) gerçekleşmesini araştırma ve Lisbon antlaşmasıyla AÖGAB’ın tüm yapısına sunulan değişiklikleri değerlendirme amacı taşımaktadır. Burada AÖGAB’in kurumsal yapısı, karar verme yöntemi, hukuki enstrümanların temel yapısı ve hukuki efekti, her bir bölgedeki gelişmeler ve sonda bireysellerin hukuki korunması durumu incelenmiş. Bölge araştırması AÖGAB’in Amsterdam antlaşmasında hedefe alındığı ve söz verildiği gibi başarılı kurulmadığını tespıt etmiş. Değerlendirme AÖGAB’in mevcut sisteminde noksanlar tespit etmiş. AÖGAB’in mevcut sistem boşlukları şunlardır: AÖGAB’in siyaset alanlarının Avrupa Birliğinin farklı sütununda bulunması karışıklığa ve şeffaflık eksikliğine yol açıyor; üçüncü sütün hukuki enstrümanların temel yapısı ve hukuki etkisi verimsizliğe yol açıyor; Avrupa Parlamentosunun karar verme mekanizmasında bulunmaması üçüncü sütun hukuki enstrümanların gayri meşruluğuna yol açıyor; Avrupa Adalet divanının AÖGAB’in IV’ üncü başlık ve üçüncü sütun önlemleri üzere sınırlı ön duruşma yetkisi ve üçüncü sütun organları fiilleri üzere ön duruşma yetkisizliği; bireysellere üçüncü sütun önlemleri direk olarak itiraz etme hakı verilmemiş. Lizbon Antlaşması AÖGAB’in hukuki, işletme ve yargılama sistemini birleştiriyor. Antlaşma AÖGAB’inde hukuki enstrümanların homojen bir yapısını oluşturuyor, ortak karar verme prosedürünü tüm hukuki fiillere uyguluyor, Avrupa Adalet Divanının yetkisini genişletiyor ve Temel haklar tüzüğünü AB’ye sunuyor. Bu temel haklar sorumluluğu taşıyan ve hukuki incelenen önlemleri ile daha verimli, şefaf, hukuki meşru bir bölgenin oluşmasına yardımcı olacaktır.

The primary aim of the thesis was to examine the realisation of the Area of freedom, security and justice in the European Union introduced by the Treaty of Amsterdam and to evaluate the modifications introduced by the Lisbon Treaty to the whole structure of the AFSJ. The institutional structure, the decision making process, the nature and legal effects of the legal instruments, the developments in each of the areas and finally the situation with judicial protection of individuals in the AFSJ have been examined. The research of the area revealed that the establishment of the AFSJ was not completed successfully as was intended and promised by the Treaty of Amsterdam. The evaluation detected the shortcomings in the present system of the AFSJ. The gaps in the present system of the AFSJ are: the existence of AFSJ policies within different pillars of the EU leads to complexity and to the lack of transparency; the nature and legal effects of the third pillar legal instruments in the AFSJ leads to inefficiency; non-involvement of the European Parliament in the decision making causes illegitimacy of the third pillar measures; the limited preliminary ruling jurisdiction of the European Court of Justice over Title IV and the third pillar measures of the AFSJ and no jurisdiction to review third pillar agencies acts; the individuals are not given locus standi to challenge third pillar measures directly. The Lisbon Treaty unifies the legal, operational and judicial structure of the AFSJ. It creates a homogenous structure of legal instruments in the AFSJ, extends co-decision procedure to all legal acts, broadens the jurisdiction of the ECJ, and incorporates the Charter of fundamental rights into the EU. It will promote a more efficient, transparent, legitimate area with judicial scrutiny of measures and their accountability with fundamental rights.
Keywords: Avrupa Birliği Hukuku; Avrupa Birliği_Hukuk; Güvenlik_Hukuk; Özgürlük